2013
DOI: 10.1074/jbc.r113.481549
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Proprotein Convertases: Their Unique, Redundant, Complementary, and Opposite Functions

Abstract: The secretory proprotein convertase (PC) family comprises nine members: PC1/3, PC2, furin, PC4, PC5/6, PACE4, PC7, SKI-1/S1P, and PCSK9. The first seven PCs cleave their substrates at single or paired basic residues, and SKI-1/S1P cleaves its substrates at non-basic residues in the Golgi. PCSK9 cleaves itself once, and the secreted inactive protease escorts specific receptors for lysosomal degradation. It regulates the levels of circulating LDL cholesterol and is considered a major therapeutic target in phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
175
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 104 publications
2
175
0
Order By: Relevance
“…We asked whether the known cleavage sequence could be recognized and cut if placed elsewhere within the prodomain, anticipating that such engineering might generate a more active protease. We posed this hypothesis based on the typical processing pathway of proprotein convertases; most members of this family of proteases undergo two cleavage events to mature (32). The first event, common to all convertases including PCSK9, cuts the prodomain from the catalytic domain, allowing the prodomain to serve both as a chaperone for delivery of the convertase to its proper cellular compartment and a self-inhibitor of proteolytic activity (33).…”
Section: The Pcsk9 Catalytic Domain Can Perform Intermolecularmentioning
confidence: 99%
“…We asked whether the known cleavage sequence could be recognized and cut if placed elsewhere within the prodomain, anticipating that such engineering might generate a more active protease. We posed this hypothesis based on the typical processing pathway of proprotein convertases; most members of this family of proteases undergo two cleavage events to mature (32). The first event, common to all convertases including PCSK9, cuts the prodomain from the catalytic domain, allowing the prodomain to serve both as a chaperone for delivery of the convertase to its proper cellular compartment and a self-inhibitor of proteolytic activity (33).…”
Section: The Pcsk9 Catalytic Domain Can Perform Intermolecularmentioning
confidence: 99%
“…6,7,15,16 After the discovery of PCSK9 and its relationship to circulating levels of LDL-cholesterol (LDL-C), 12,14 a race was sparked around the world to find not only new gain-of-function (GOF) mutations causing hypercholesterolemia 14,17 but also loss-of-function (LOF) mutations compatible with hypocholesterolemia. 18,19 The highly active Anglo-Saxon D374Y PCSK9 variant is the most remarkable GOF mutation,…”
mentioning
confidence: 99%
“…From 1990 to 1999, 8 mammalian PCs were discovered and shown to be responsible for the tissue-specific processing of various secretory precursors. 6,7 Substrates of these PCs include hormones, growth factors, receptors, metalloproteases, membrane-bound transcription factors, and surface glycoproteins. Thus, depending on their site of action and protease activities, 8 PCs are vitally involved in different physiological and clinically relevant processes, 9,10 resulting in activation/inactivation events, some of which affect cardiovascular health.…”
mentioning
confidence: 99%
“…Without a doubt, the 14-year story that began in 2003 with the description by Seidah [34][35][36][37][38] of the protease initially called NARC-1-now PCSK9-and its most advanced saga, the March 2017 publication of the study FOURIER "Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk" (NCT01764633) [39] with evolocumab is the most fascinating story of current cardiology. Using an approach wich blocks the protein PCSK9 from binding to the LDLR and thus enhancing LDLR recycling, the authors demonstrated a third approach to reducing ASCVD through LDL-C reduction.…”
Section: Inhibition Of Pcsk9mentioning
confidence: 99%